Application of the ALARA Principle to Minimize Collective Dose in NPP Accident Management within the Containment - Bogorad, V.; Slepchenko, O.; Kyrylenko, Y. (Ядерна та радіаційна безпека, 2016)
This research focuses on application of the ALARA principle to minimize the collective doses (both for NPP personnel and the public), relating to admission of personnel to the containment for accident management activities and depending on operation of ventilation systems. Results from assessment of radiation consequences are applied to a small-break LOCA with failure of LPIS at VVER-1000 reactors. The public doses are evaluated using up-to-date RODOS, MACCS and HotSpot software for assessment of radiation consequences. The personnel doses are evaluated with MicroShield and InterRAS codes. The time function and optimal value of the collective dose are defined. The developed approach can be applied for minimization of the collective dose for optimization of accident management strategies at NPPs.